The forgotten Narrative of H.M.S. Challenger and the implications for decapod nomenclature - Froglia, Carlo; Clark, Paul F. (Zootaxa, 2011)
The Narrative of the Challenger cruise was published in 1885 and contained valid descriptions of crustacean decapod taxa. While C.S. Bate (Challenger Macrura) mentioned the discovery of new taxa without making them valid, J.R. Henderson (Anomura) and E.J. Miers (Brachyura) provided short descriptions including figures that made several new names available. With a few exceptions, these valid scientific names together with their date of availability have been overlooked by almost all subsequent taxonomic studies. Consequently the decapod taxa named in the Challenger Narrative are listed and the implications for nomenclature in each case are discussed.